แนวทางการดำเนินงานนิเทศภายในโรงเรียนแม่วินสามัคคี อำเภอแม่วาง จังหวัดเชียงใหม่ - สมพิศ ศรีชมภู (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This independent study has 2 objectives which are 1) to study the problems and suggestion of collegial supervision in Maewinsamakkee School, Mae Wang District, Chiang Mai Province and 2) to study the guidelines for Collegial Supervision in Maewinsamakkee School, Mae Wang District, Chiang Mai Province.There are 3 procedures of this study. 1) study the problems and suggestion of collegial supervision in Maewinsamakkee School, Mae Wang District, Chiang Mai Province. The population used in this study were 36 teachers of Maewinsamakkee School in the academic year 2557. The tools used in this study was questionnaires and the data was analyzed by using average and percentage. 2) study and draft the guidelines for Collegial Supervision in Maewinsamakkee School. The populations used in this study were administrators or involves supervision outstanding from the school’s collegial supervision. The tools used in this study were questionnaire and the data was analyzed by inductive inference. 3) examine the guideline of collegial supervision. The populations for this study were 5 experts and the tools used in this study were the examination form of possibility, suitability, and usefulness. The data was analyzed by using average (µ) and standard deviation (σ). The findings found that the conditions of collegial supervision in Maewinsamakkee School, Mae Wang District, Chiang Mai Province was problematic. Considering each aspect it was found that all four of the collegial supervision was as follows : administrator and teachers lack of awareness about the project procedures of collegial supervision, current state of collegial supervision, problems and actual needs for supervision. The problem of collegial supervision in Maewinsamakkee school found that the data analysis based on various aspects also has little practice and a lack of clarity, administrators and teachers are not involved in targeting the collegial supervision , no meetings were planned for supervision ,teachers were not involved in planning and projects for the collegial supervision, administrator do not oversee themselves, supervisors lacked the knowledge and understanding about collegial supervision and lacked information from evaluation to develop and improve operations to achieve better supervision. The guidelines of collegial supervision in Maewinsamakke School, Mae Win District focused on the committee’s responsible to clearity, planned by the participation of teachers and school personnel, action supervision in a defined continuous calendar, to target the supervision and inform teachers and school personnel clearly, as well as to evaluate and report the results to teachers and school personnel to improve development operations even further. The results of possibility, suitability and usefulness were at the highest level.